2002
DOI: 10.1124/jpet.102.037135
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Stability and In Vivo Pharmacokinetic Studies of a Model Opioid Peptide, H-Tyr-d-Ala-Gly-Phe-d-Leu-OH (DADLE), and Its Cyclic Prodrugs

Abstract: In vitro stability and in vivo pharmacokinetic studies of a model opioid peptide, H-Tyr-D-Ala-Gly-Phe-D-Leu-OH (DADLE), and its cyclic prodrugs (acyloxyalkoxy-based cyclic prodrug of DADLE, coumarinic acid-based cyclic prodrug of DADLE, and oxymethyl-modified coumarinic acid-based cyclic prodrug of DADLE) were conducted. The enzymatic stability of DADLE and its prodrugs in various biological media was determined at 37°C in the presence and absence of paraoxon, a known esterase inhibitor. The prodrugs exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…Very low levels of DADLE derived from its prodrugs were observed in the brain after 240-s perfusion. These results are consistent with the in vitro stability studies reported previously by our laboratory (Yang et al, 2002b). According to a simulation model described by Anderson (1996) for prodrug-to-drug bioconversion in plasma and the brain, brain selectivity of prodrug bioconversion is a prerequisite for enhancement of brain delivery of a parent compound.…”
Section: Compoundsupporting
confidence: 83%
See 2 more Smart Citations
“…Very low levels of DADLE derived from its prodrugs were observed in the brain after 240-s perfusion. These results are consistent with the in vitro stability studies reported previously by our laboratory (Yang et al, 2002b). According to a simulation model described by Anderson (1996) for prodrug-to-drug bioconversion in plasma and the brain, brain selectivity of prodrug bioconversion is a prerequisite for enhancement of brain delivery of a parent compound.…”
Section: Compoundsupporting
confidence: 83%
“…administration in rats (Yang et al, 2002b). As expected from the in vitro cell permeation studies described above, the brain uptake after i.v.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Scheme 15. Cyclic two-step prodrugs of peptides based on: (A) the "trimethyl lock" [80,81] and, (B) coumarinic acid derivatives [85][86][87][88][89][90][91]. Another approach, quite similar to the "trimethyl lock" concept, for the design of two-step prodrugs has been based on coumarinic acid derivatives, as these equally undergo facile lactonization [83].…”
Section: Two-step Activationmentioning
confidence: 99%
“…The most relevant example of application of such coumarinic acid derivatives concerns cyclic proprodrugs of the opioid peptide DADLE (22), depicted in Scheme 15B [85,86]. This approach was also employed to oxymethyl-modified cyclic pro-prodrugs of DADLE (23, Scheme 15B), designed to promote better intrinsic cell permeation while preserving the desired sensitivity to esterases [87][88][89][90][91], and to RGD peptidomimetics [92].…”
Section: Two-step Activationmentioning
confidence: 99%